Tibiofemoral Contact Mechanics with Horizontal Cleavage Tear and Resection of the Medial Meniscus in the Human Knee. (2nd November 2016) - Koh, Jason L.; Yi, Seung Jin; Ren, Yupeng; Zimmerman, Todd A.; Zhang, Li-Qun
Abstract : Background: The meniscus is known to increase the contact area and decrease contact pressure in the tibiofemoral compartments of the knee. Radial tears of the meniscal root attachment along with partial resections of the torn meniscal tissue decrease the contact area and increase pressure; however, there is a lack of information on the effects of a horizontal cleavage tear (HCT) and partial leaf meniscectomy of such tears on tibiofemoral contact pressure and contact area. Methods: Twelve fresh-frozen human cadaveric knees were tested under 10 conditions: 5 serial conditions of posterior medial meniscectomy (intact meniscus, HCT, repaired HCT, inferior leaf resection, and resection of both inferior and superior leaves), each at 2 knee flexion angles (0° and 60°) under an 800-N axial load. Tekscan sensors (model 4000) were used to measure the contact pressure and contact area. Results: HCT and HCT repair resulted in small changes in the contact area and an increase in contact pressure compared with the intact condition. Resection of the inferior leaf resulted in significantly decreased contact area (to a mean 82.3% of the intact condition at 0° of flexion and 81.8% at 60° of flexion; p < 0.05) and increased peak contact pressure (a mean 36.3% increase at 0° flexion and 43.2% increase at 60° flexion; p < 0.05) in the medial compartment. Further resection of the remaining superior leaf resulted in additional significant decreases in contact area (to a mean 60.1% of the intact condition at 0° of flexion and 49.7% at 60° of flexion; p < 0.05) and increases in peak contact pressure (a mean 79.2% increase at 0° of flexion and 74.9% increase at 60° of flexion; p < 0.05). Conclusions: Resection of meniscal tissue forming the inferior leaf of an HCT resulted in substantially decreased contact area and increased contact pressure. Additional resection of the superior leaf resulted in a further significant decrease in contact area and increase in contact pressure in the medial compartment. Clinical Relevance: Repair or minimal resection of meniscal tissue of an HCT may be preferred to complete leaf resection to maintain knee tibiofemoral contact mechanics.